Analisa Faktor yang Mempengaruhi Cash Holding pada Perusahaan Manufaktur yang Terdaftar Pada Bursa Efek Indonesia - Dita Ayu Nurani; Henny Setyo Lestari (J-MAS (Jurnal Manajemen dan Sains), 2022)
The decision to hold cash in the company is a very important financial decision that a company needs to pay attention to. The level of cash holding of a company not only describes the state of the company's business plan and financial strategy, cash holding is related to the company's internal structure and external environment. Companies that have cash can start well and can prevent all risks, while complementing the needs of daily operations and trading activities. This means that companies can use their cash holdings to identify investment opportunities and at the same time, they can allocate capital efficiently to avoid risks caused by operating cash flows. This study aims to see the effect of cash holding on manufacturing companies. The independent variables in this study are firm size, financial leverage, substitute for non-liquid assets, cash flow, capital expenditures, dividend payments. The dependent variable in this study is cash holding. This study uses panel data analysis and is carried out by collecting data from 31 manufacturing companies in Indonesia in the period 2016 to 2021. This study finds a negative relationship between financial leverage, substitution of liquid assets, cash flow, dividend payments to cash flow. while the size of the company, capital expenditures do not have a significant relationship with cash holding.